Covid-19 pandemic policy monitor (COV-PPM) - European level tracking data of non-pharmaceutical interventions - Kayvan Bozorgmehr (Elsevier, 2021)
The Covid-19 Pandemic Policy Monitor (COV-PPM) dataset prospectively documents non-pharmaceutical interventions (NPIs) taken to contain SARS-Cov-2 transmission across countries in EU27, EEA and UK. In Germany, measures have also been recorded at the federal state and, partially, at the district levels. NPIs implemented since January 2020 have been retrieved and updated weekly from March 2020, from official governments webpages, Ministries of Health, National (Public) Health Institutes or Administrations. NPI categories collected refer to restrictions, closures or changes in functioning implemented in 13 domains: public events (gatherings in indoor or outdoor spaces); public institutions (kindergartens, schools, universities); public spaces (shops, bars, restaurants); public transport (trains, buses, trams, metro); citizens movement/mobility (e.g. pedestrians, cars, ships); border closures (air, land or sea, all incoming travels, from high-risk regions, only non-nationals); measures to improve the healthcare system (e.g. human resources or technical reinforcement, redistribution, material or infrastructural); measures for risk/vulnerable groups (e.g. elderly, chronically ill, pregnant); economic measures (e.g. lay-off rules establishment, actions to avoid job-loss, tax relaxation); testing policies (e.g. testing criteria changes); nose and mouth protection rules, vaccination and others/miscellaneous measures.